BINATIONAL MARRIAGES AND MULTICULTURAL EDUCATIONAL ENVIRONMENT - Sowa-Behtane, Ewa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Today, in the era of post-modernity, the ethnically, racially, religiously, culturally or nationally mixed marriages are more and more frequent phenomenon, contributing to the emergence of new types of cultural identity. Nationally mixed marriages (binational) define a new cultural quality when they do not concern only individuals, but when they become a phenomenon which is statistically frequent, and even dominant in a broader social context. The aim of the current project is an academic description of binational marriages which have been concluded by spouses from different nationalities, and thus characterized by different culture, tradition, mother tongue, and often religion and race, one of them being the representative of Polish culture.